The Impact of Critical-Creative Thinking and Simurelay-Based Motivation on Motor Installation Learning Outcomes - Mahardika, Dwi; Haryudo, Subuh Isnur; Wrahatnolo, Tri; Sumbawati, Meini Sondang (Edukasi, 2025)
This study explored the correlation of critical thinking, creative thinking, and Simurelay-based learning motivation to the learning outcomes of students in class XI TITL at SMKN 7 Surabaya. The research used an ex post facto method with a correlational design. Participants were class XI students in the Electrical Power Installation Engineering program. Data were collected using questionnaires and tests, and analyzed with regression techniques using SPSS. The results showed that critical thinking significantly influenced knowledge (78.9%), attitude (70.2%), and skills (2.6%). Creative thinking contributed to knowledge (18.2%) and attitude (24%), but has limited effect on skills (3.6%). Learning motivation affected knowledge (19%), attitude (24.8%), and skills (5%). Combined, all three factors influenced learning outcomes: knowledge (98.3%), attitude (98.4%), and skills (8.9%). These findings underlined the importance of cognitive abilities and motivation in vocational education. The integration of critical and creative thinking with Simurelay-based learning enhanced engagement and achievement across cognitive, affective, and psychomotor domains. Such strategies were essential for improving technical learning performance.